PENDUGAAN VOLUME TEGAKAN BERDASARKAN JUMLAH DAN KERAPATAN TAJUK PADA FOTO UDARA - Ishak Sumantri; Haryono Haryono; Machfudh Machfudh (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
SummaryThe relationship description of stumpage volume over the crown densities and number of crown which is measured on serial photos are the object of this study. The study was conducted research take at a tropical rain forest which have been harvested by using the Indonesia Selective Cutting (TPI) system in East Kalimantan. The model analysis reveals that:1. The distribution of crown densities (%) and number of crown data are normally distributed.2. The relationship of stumpage volume over the crown densitys percentage and number of crown can be expressed as: V = -169. 7132 + 3.8514N + 2.8532 + 0.0004C2 + 0.014CNWhere: V : Stumpage volume, (m3)N : Numbers of crown, unitlessC : Crown, densitys, %.Coefficient of determination (R) = 0. 7828. This model is significant at 95% level after tested by F-test.3. The model and its analysis only valid in East Kalimantan.